Inadvertent - Knausgård, Karl Ove, 1968- (Why I write series., 2018)
"Why I Write" may prove to be the most difficult question Karl Ove Knausgaard has struggled to answer yet it is central to the project of one of the most influential writers working today. To write, for the Norwegian artist, is to resist easy thinking and preconceived notions that inhibit awareness of our lives.